Characterization of antarctic bacteria and their antimicrobial activities - Tam, Heng Keat (2009)
A total of 2582 bacterial strains were isolated from 16 soil and water samples from the King George Island and Schirmacher Range, Antarctica. Twenty three Antarctic bacterial strains inhibited the growth of one or more Gram-negative and Grampositive food pathogens such as Escherichia coli O 157: H7, Salmonella spp., Klebsiella pneumonia, Enterobacter cloacae and Vibrio spp. and a Gram-positive food pathogen Bacillus cereus K15. Seven out of the 23 strains, SGS, CG21, HKAM1, MTC3, MA2, WEAl and WEKl were identified based on their 16S rDNA sequences and biochemical analyses. They were Pseudomonas sp. MTC3, Pseudomonas sp. CG21, Pseudomonas sp. MA2, P. corrugata WEKl, P. migulae WEAl, Janthinobacterium lividum HKAMl and Pedobacter cryoconits SGS. Although most of them were affiliated to the same genus or closely related species, their biochemical, phenotypic characteristics and antibiotics resistance profiles varied. Inhibitors produced by strains MTC3, CG21 and SGS were sensitive to protease suggesting that they have proteinaceous structures while strains WEAl, WEKl, HKAMl and MA2 were not sensitive to catalase, lipase, aamylase, and protease indicating four of these inhibitors have complex structures. Three out of seven Antarctic bacterial strains WEAl, WEK1 and MA2 were found to encode polyketide synthase gene, indicating the antimicrobial agent was probably produced by polyketide synthase. Antimicrobial resistance profiles of 45 Antarctic bacterial isolates were obtained. Most of the bacteria were resistance to at least of three or more types of antimicrobial agents tested while one of the bacterial isolate was susceptible to all the antimicrobial agents. These data revealed that the existence of many antimicrobial resistant strains among the Antarctic bacterial population. The plasmid sequence of pH Kl of Pseudomonas sp. CG21 revealed that there was no gene encoding the antimicrobial production and antimicrobial resistance on the plasmid. Basically the pHKl plasmid carried genes encoding for plasmid replication, stability and maintenance, mobilization and genes for unknown function.